Study of Driving Torque through Dynamic Analysis of Robot - Taek OH, Yeon; ., . (International Journal of Engineering and Technology, 2018)
These days, the interests on the low-cost handling robots are increasing because it is important to get down the unit cost of production to get the price competitiveness. The robot joint with simple mechanism is more suitable to implement the low-cost robot system as well known. The moving parts of robot have to be designed for simple and robust. But the dynamic characteristics analysis is induced by the robot links because they drive in high acceleration and deceleration. In this reason, the dynamic characteristics analysis of the high-speed robot is very important in the design process. In this paper, the study on robot driving torque analysis of a articulated robot has been done and the research results will be introducedÂ Â Â